2014
DOI: 10.1021/jp503339g
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Organization of Cytochrome c2 near the Binding Domain of Cytochrome bc1 Studied by Electron Spin–Lattice Relaxation Enhancement

Abstract: Measurements of specific interactions between proteins are challenging. In redox systems, interactions involve surfaces near the attachment sites of cofactors engaged in interprotein electron transfer (ET). Here we analyzed binding of cytochrome c2 to cytochrome bc1 by measuring paramagnetic relaxation enhancement (PRE) of spin label (SL) attached to cytochrome c2. PRE was exclusively induced by the iron atom of heme c1 of cytochrome bc1, which guaranteed that only the configurations with SL to heme c1 distanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…Our results indeed coincide with the fact that electron transfer can be readily initiated from the b-heme without the need for close contact with an external electron acceptor such as quinones or molecular oxygen. (6) It was also reported that the axial histidylimidazole ligands of the b L heme have a distinct ionic character, 40 which would favour electron transfer processes. This electronegative character of at least one of the two His ligands was explained by the presence of nearby arginine residues.…”
Section: Heme Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results indeed coincide with the fact that electron transfer can be readily initiated from the b-heme without the need for close contact with an external electron acceptor such as quinones or molecular oxygen. (6) It was also reported that the axial histidylimidazole ligands of the b L heme have a distinct ionic character, 40 which would favour electron transfer processes. This electronegative character of at least one of the two His ligands was explained by the presence of nearby arginine residues.…”
Section: Heme Bmentioning
confidence: 99%
“…1 The cyt bc 1 complex is a dimer whose monomer comprises four key elements that are directly involved in the electronic pathway (Fig. 1): (1) the heme c 1 is located near the intermembrane-space side of the membrane; it is situated near the cyt c docking interface and serves as an electron donor for the reduction of cyt c; 2,[5][6][7] (2) the Rieske iron-sulfur cluster mediates electron transfer between the quinol at the Q o site and the heme c 1 via a series of conformational changes; 1 (3) and (4) the hemes b L and b H that mediate electron transfer between the two quinone binding sites, Q o and Q i sites. 2 Depending on the reaction stage, the three iron centers of the hemes are found in either their ferric (Fe(III)) or ferrous forms (Fe(II)) and are all characterized by a 6-coordinated (6-c) lowspin state, therefore minimizing the reorganization energy required to undergo the electron transfer.…”
Section: Introductionmentioning
confidence: 99%
“…At ionic strength typical of physiological conditions, the complexes are very short-lived and the stationary concentration of bound cytochrome c is low. This implicates a mechanism in which under physiological conditions cytochrome c does not form stable, longlived complexes but rather constantly collides with the surface of cytochrome bc 1 and electron transfer takes place coincidentally with one of such collision (117,206,221).…”
Section: Cytochrome C Binding Sitementioning
confidence: 99%
“…The transient binding of cytochrome c to cytochrome bc 1 in solution was inferred from the analysis of electron transfer between these proteins (175) and from the measurements based on the techniques that were independent of electron transfer, such as plasmon wave-guide resonance spectroscopy (75) or EPR (206,221,224).…”
Section: Cytochrome C Binding Sitementioning
confidence: 99%
“…EPR spectroscopy was performed on a Bruker Elexsys E580 spectrometer operating at X- and Q-bands using similar equipment and settings as described previously in ref. 26 and 35. CW spectra were recorded at the X-band over the temperature range 20–120 K using a non-saturating microwave power.…”
Section: Methodsmentioning
confidence: 99%